Research on the Communication Path of Public Opinion in University Ideological and Political Network for Big Data Analysis. (7th July 2022) - Xu, Shengyu; Liu, Jiayu; Chen, Kan; Yang, Yuling
Abstract : In recent years, with the rapid development of information technology, the Internet has gradually become an interactive platform for people to exchange ideas, collide emotions, spread information, and release emotions. The openness, anonymity, and inclusiveness of the Internet have reduced the obstacles of information dissemination and triggered the conflict of public opinion on the Internet. In addition, students actively express their opinions, attitudes, and feelings on important topics in life and study on the Internet, forming a certain scale of online opinions reflecting students' unique political attitudes, moral concepts, and values. Because college students are immature physically and mentally and the network environment is full of phenomena, it is easy to arouse their emotional resonance. Therefore, the free and diverse network environment presents new challenges and higher requirements of the times for the stable operation of college network public opinion guidance. Therefore, how to form systematic education in universities combined with ideological and political network public opinions under big data has become an important problem to be solved. Based on this paper presents the communication pattern of network public opinion and model it, namely, the random network public opinion transmission model. By comparing the scope and influence of the two transmission paths of network public opinion, the paper draws the conclusion and strengthens the teaching practice of ideological and political courses. Finally, it is pointed out that the research of the ideological and political network public opinion communication path is a complex digital communication system project, which requires the government, the media, and the schools together to give suggestions in the guidance of the network public opinion.